2015
DOI: 10.3892/ol.2015.3812
|View full text |Cite
|
Sign up to set email alerts
|

Successful chemotherapy with carboplatin and nab-paclitaxel for thymic large cell neuroendocrine carcinoma: A case report

Abstract: Abstract. Thymic large cell neuroendocrine carcinomas (LCNECs) are rare, and the optimal regimen for second and subsequent lines of chemotherapy for the treatment of LCNECs remains unknown. In the present case study, a 59-year-old male with post-operative recurrent thymic LCNEC was treated with nab-paclitaxel and carboplatin every 4 weeks as third-line chemotherapy, and a partial response was achieved following 4 cycles of this regimen. The patient developed grade 4 neutropenia and grade 3 leukopenia, but none… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…It has been also proved to be effective in lung neuroendocrine carcinoma. [ 21 23 ] After progression in the liver, the patient was given nab-paclitaxel plus erlotinib which eased the patient's symptom and led to partial remission. This regimen also demonstrated significant activity during the second progression and prolonged his survival.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also proved to be effective in lung neuroendocrine carcinoma. [ 21 23 ] After progression in the liver, the patient was given nab-paclitaxel plus erlotinib which eased the patient's symptom and led to partial remission. This regimen also demonstrated significant activity during the second progression and prolonged his survival.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both our patients had an ECOG PS of 2 at the initiation of combination chemotherapy; therefore, this combination therapy and maintenance therapy with nab −paclitaxel is feasible for patients with a poor PS and advanced thymic carcinoma. Furthermore, this is the first report to demonstrate that combination chemotherapy comprising carboplatin plus nab −paclitaxel and maintenance therapy with nab −paclitaxel is effective for undifferentiated thymic carcinoma, a rare type of thymic carcinoma, although previous reports had showed the efficacy of this treatment in other subtypes of thymic carcinoma [ 10 , 11 , 12 , 13 ]. Several retrospective [ 3 , 4 ] and prospective [ 5 , 6 , 7 ] studies have reported that carboplatin plus solvent-based paclitaxel is an effective treatment for thymic cancer.…”
Section: Discussionmentioning
confidence: 95%
“…To date, 19 cases of resection for thymic LCNEC have been reported in the English language literature [[6], [7], [8], [9], [10], [11], [12], [13], [14], [15]]. The author summarized a total of 20 patients, including the present case, with ages between 42 and 90 (mean age, 57) years (Table 1).…”
Section: Discussionmentioning
confidence: 98%